2023
DOI: 10.3390/electronics12153354
|View full text |Cite
|
Sign up to set email alerts
|

Cascading and Ensemble Techniques in Deep Learning

Abstract: In this study, we explore the integration of cascading and ensemble techniques in Deep Learning (DL) to improve prediction accuracy on diabetes data. The primary approach involves creating multiple Neural Networks (NNs), each predicting the outcome independently, and then feeding these initial predictions into another set of NN. Our exploration starts from an initial preliminary study and extends to various ensemble techniques including bagging, stacking, and finally cascading. The cascading ensemble involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Skin cancer ranks among the most prevalent forms of cancer globally, making up around a third of all reported cancer diagnoses, with its frequency steadily rising each year [ 4 ]. Just in the United States, it is estimated that more than 9500 individuals receive a skin cancer diagnosis daily [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin cancer ranks among the most prevalent forms of cancer globally, making up around a third of all reported cancer diagnoses, with its frequency steadily rising each year [ 4 ]. Just in the United States, it is estimated that more than 9500 individuals receive a skin cancer diagnosis daily [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that one of the main advantages of ensembles over individual models is their ability to achieve higher-quality indicators of data processing. By aggregating the results of different underlying algorithms, it becomes possible to level out the erroneous predictions obtained from individual models [3]. However, in practice, there are situations where poorly trained classifiers can degrade the results compared to the application of individual algorithms [4].…”
mentioning
confidence: 99%
“…The papers provide various ways of combining ensemble models, but their selection and building are empirical, which does not make it possible to transfer the experience to other subject areas and data structures [2,3]. Another problem with ensemble approaches is that setting optimal parameters requires considerable knowledge and experience and many analysis procedures [4,5].…”
mentioning
confidence: 99%